Self-Medication Practices and Health Seeking Behaviour among Residents of Selected Villages in A Block of West Bengal: A Mixed-Methods Study - Vineeta Shukla; Kuntala Ray; Sinjita Dutta; Mausumi Basu (Indian Association of Preventive and Social Medicine, 2022)
Introduction: Self-medication can lead to problems such as adverse effects and antibiotic resistance. This study was conducted to estimate the proportion of self-medication practice, to elicit the reasons for practicing self-medication, to find the factors associated with self-medication practice and to assess the health seeking behaviour among a rural community of West Bengal. Method: A study with mixed-methods approach was conducted among 212 households from four selected villages in a block of West Bengal. Focussed Group Discussions were held with respondents who were practising self-medication. Data were analysed using SPSS 25.0 and Atlas ti 7.0. Multivariable logistic regression was performed to find the factors associated with self-medication practice. Results: The proportion of self-medication practice was found to be 41%. Allopathy was most commonly preferred system of Medicine (78.8%). Statistically significant factors associated with self-medication practice were education upto Middle school (aOR 3.59) and Secondary level (aOR 10.71), Class III socio-economic status (aOR 5.03) and presence of acute illness (aOR 28.92). Conclusion: Proportion of self-medication practice among rural population was high. This needs to be addressed and health education should be provided to them.